Influence of different box preparations on creep performance of corrugated fibreboard boxes subject to constant and cycling relative humidity environments - Gray-Stuart EM; Wade K; Redding GP; Parker K; Bronlund JE (John Wiley and Sons, Ltd, 2022)
To understand the effect of load and relative humidity (RH) on box creep in cool storage conditions, standard tests are performed. However, these test conditions are oversimplified compared with actual shipping conditions. Our aim is to develop test conditions that more closely mimic those encountered during refrigerated conditions to investigate their influence on creep performance and box lifetime. We compared three box preparations: (i) empty boxes used as a control, (ii) filled boxes, and (iii) boxes with only two side panels exposed to the atmosphere. A controlled environment test facility was used to subject sets of 24 boxes to 30% of their ultimate failure load under different cyclic and constant relative humidity conditions. Results indicate that filled boxes had substantially reduced performance in terms of secondary creep rate and lifetime. The fill in the box contributed to out-of-plane displacement of the side panels which manifested earlier than in the control, resulting in a higher creep rate. Boxes with only two exposed panels had lower moisture uptake and performed substantially better than the control. These findings demonstrate how creep performance and box lifetime depend on the box conditions including fill and the area of the box that is exposed for moisture transfer. Alternative box preparations which mimic supply chain conditions are worthy of investigation in creep analysis as they will help predict more accurately box performance in the cold supply chain.